The Influence of Leadership Style and Work Environment on Work Discipline and its Impact on the Performance of State Civil Employees in the District Regional Tax and Retribution Management Agency of Muaro Jambi District - M. Zahari; Ali Akbar; M. Reval Aji Prayudha (Dinasti Publisher, 2023)
The purpose of this research is to describe the leadership style, work environment, discipline and performance of employees of the Muaro Jambi Regency Regional Tax and Levy Management Agency and to analyze the partial and simultaneous direct and indirect influence of leadership style and work environment on employee discipline and performance, as well as to analyze discipline towards employee performance. The population in this research are employees of the Muaro Jambi Regency Regional Tax and Levy Management Agency, totaling 44 employees with conditions in 2022. The data analysis technique used in this research is through path analysis followed by hypothesis testing through the F test (Simultaneous) and t (Partial). From the path analysis tests carried out, it was found that leadership style and work environment had an influence on discipline by 79.39% while the rest was influenced by other variants. Leadership style and work environment have an influence of 80.72% on employee performance at the Muaro Jambi Regency Regional Tax and Levy Management Agency. This research concludes that the leadership style, work environment, discipline and employee performance are in good and high condition. Apart from that, the leadership style and work environment partially and simultaneously have a positive and significant influence on employee discipline and performance at the Muaro Jambi Regency Regional Tax and Levy Management Agency. Likewise, discipline has a positive and significant influence on employee performance.